IZIN LINGKUNGAN: SUATU KAJIAN PERBANDINGAN PERATURAN PERUNDANG-UNDANGAN - Djiwandana, Alif Djangkung; Firmansyah, Mochammad Erga (CV. Era Digital Nusantara, 2023)
Management of resources in an area always requires licensing, where a permit is needed to take the first steps in managing resources or the environment in an area. This has actually been regulated in the UUPPLH and the Job Creation Law, but in these two regulations, the permits are different, where the UUPPLH is more on the environmental document process (Environmental Impact Analysis/Amdal) while the Job Creation Law simplifies the licensing process by integrating environmental permits into Business Permits. These two regulations have their respective impacts if an environmental violation of the permit occurs, the first will result in consequences for environmental permits while the second will have consequences for business permits. The Job Creation Law classifies business permits that provide warnings and high levels of care for health, safety, the environment, and resources. For this reason, The Job Creation Law remains in the public eye of various parties, even criticized and protested. Because This law is thought to only be concerned with corporations and investment, it even possibly compromises environmental law enforcement. This paper examines environmental permits in the UUPPLH and the Law on Job Creation to compare where the differences in environmental permits from the two laws are. And the author will also provide opinions regarding environmental permits from the two laws. The method used in writing this time is the Law on Job Creation main materials are legal journals that discuss licensing, the UUPPLH, and the Job Creation Law. We anticipate that this conversation will offer knowledge and understanding to the wider community about the importance of an environmental permit when it comes to managing natural resources in an area as well as an understanding of the differences in permits in the two laws.